Brazil's development cooperation: Following in China's and India's footsteps? - Finn-Ole Semrau; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2016)
The increasing importance of donor countries operating outside of the OECD's Development Assistance Committee (DAC) challenges the existing international aid architecture. In particular, non-DAC donors are suspected to provide aid solely based on self-interest without caring about recipients' need and merit. In this paper, we empirically investigate the aid allocation of one major non-DAC donor, Brazil. We find that Brazil's development cooperation is still predominantly shaped by historic and cultural ties to the Lusophone world and Latin America, while broader political and economic motives play a negligible role. To some extent, Brazil also takes recipients' need and governance into account. This broadly corroborates previous results for China and India, strengthening the conclusion that non-DAC donors are not as different from DAC donors regarding their aid motives as one might suspect.
Keywords: F35; 330; Aid Allocation; New Donors; Brazil